Early surgical outcomes of children with mechanical intestinal obstruction at Moi teaching and referral hospital, Kenya - Agade, Ivy W.; Saula, Peter W.; Maiyo, Francis (International Surgery Journal, 2024)
Background: Intestinal obstruction constitutes the largest proportion of abdominal surgical emergencies in the paediatric and adult patients in Sub-Saharan Africa, including Kenya. It is associated with high postoperative surgical complication and mortality rate in low resource healthcare systems. Methods: A prospective mixed methods study with consecutive sampling procedure was carried out from September 2021 to June 2023. Pediatric patients from birth to 14 years, with mechanical intestinal obstruction were included in the study. Categorical data was analyzed in frequencies and percentages and continuous data was analyzed using measures of central tendency and measures of dispersion. Bivariate and multivariate associations between the dependent and independent variables were assessed with a p value of less than 0.05 being statistically significant. Results: The final study population was 318 participants. Majority of participants were male with neonates comprising almost one third of participants. Classical symptoms were present in a majority of patients at initial presentation. Intussusception (34.6%) was the leading acquired aetiology of paediatric mechanical intestinal obstruction. Operative surgical management was in 94.6% of participants. Surgical complications were present in 61.1% of participants. The commonest surgical complication was surgical site infection in 16.9%. Overall mortality rate was 10.2% with 23.3% among neonates and 4.9% in older children. Referral status was statistically associated with mortality (p<0.001). Intestinal atresia had the highest case-specific mortality rate. Age, presence of comorbidity were factors associated to postoperative complications and mortality (p<0.05). Conclusions: The overall mortality rate was 10.2%. A higher mortality was seen among neonates compared to older children.